UJI ANTIOKSIDAN KOPI ROBUSTA (COFFEA CANEPHORA), BUAH STROBERI (FRAGARIA X ANNANASA), DAN KOMBINASI KEDUANYA DENGAN BERBAGAI PELARUT - Himmi Marsiati; Muhammad Arsyad; Fahreza Maulana (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Robusta coffee (Coffea canephora) and strawberries (Fragaria x annanassa) are plants containing of antioxidant. This research is aimed to determine the antioxidant activity of each plant and the combination of both plants. The activities were measured by using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method towards the extracts of ethanol, ethyl acetate, and water. The result showed that Robusta coffee beans had a value of IC50 18,96 ppm on the ethanol extract, IC50 27,03 ppm on the ethyl acetate extract, and IC50 20,13 ppm on the water extract. Strawberries had a value of IC50 173,13 ppm on the ethanol extract, IC50 211,03 ppm on the ethyl acetate extract, and IC50 205,15 ppm on the water extract. The combination of beans and strawberries had a value of IC50 42,82 ppm on the ethanol extract, IC50 55,78 ppm on the ethyl acetate extract, and IC50 41,51 ppm on the water extract. Besides, Vitamin C as the comparison standard had a value of IC50 3,68 ppm. The ANOVA test result showed a value of (p<0.05) which indicated that there were significant differences between samples and particular solvents. On the other hand, phytochemical test indicates strawberries were containing of flavonoids and phenolics.